ANALISIS PELANGGAN SMART CATERING MENGGUNAKAN METODE NET PROMOTER SCORE - Moch Rafly Wisnu Wardana; Husni Angriani; Ahyar Muawwal (KHARISMA Tech, 2023)
Smart Catering is a website-based application for food ordering services. Nowadays Smart Catering has 61 users. User experience in using Smart Catering website and the probability of users likelihood to recommend Smart Catering website can improve and maintain the existence of the website. To determine the probability of users likelihood recommend the Smart Catering website, user analysis is carried out using the Net Promoter Score (NPS) method. A survey of Smart Catering customers was conducted using 11 statements related to the level of usability of the Smart Catering website. Based on the results of the analysis that has been carried out on 45 respondent data, it shows that users of the Smart Catering website will recommend the website with a score obtained is 55.09% in terms of the usability aspect of the Smart Catering website.